Laser synthesis of ultracold alkali metal dimers: optimization and control. (October 2015) - Pazyuk, E A; Zaitsevskii, A V; Stolyarov, A V; Tamanis, M; Ferber, R
Abstract : The review concerns the potential of modern high-resolution laser spectroscopy and state-of-the-art ab initio electronic structure calculations used to obtain comprehensive information on the energy and radiative properties of strongly coupled rovibronic diatomic states. The possibility of deperturbation treatment of the intermediate electronically excited states at the experimental (spectroscopic) level of accuracy is demonstrated taking alkali metal dimers as examples. The deperturbation analysis is of crucial importance to optimize multistep laser synthesis and stabilization of ultracold molecular ensembles in their absolute ground level. The bibliography includes 227 references.